Avaliação do desgalhador florestal de discos em função de diferentes teores de umidade da madeira de eucalipto - Tonin, Rodrigo Petrongari [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Considering the growth of the Brazilian economy since the 90s, the Brazilian forest sector has undergone several changes as the deployment of modern machines throughout the production process. For the forestry sector the activities considered the most important is the harvesting, since it is the most costly, more than 50% of production costs. With the introduction of mechanized harvesting in Brazil, further studies become necessary to obtain real data on the new machines emerging in the forestry market. The objective of this study was to perform the technical and economic evaluation of a disk forest delimber as well as to evaluate the effectiveness of delimbing in different treatments (time (days)). For the technical analysis has been conducted a study about time and motion, where the method used to perform the data collection was the continuous-time timing method, for economic analysis, the operating costs of the system have been calculated through the proposed method by ASABE and the effectiveness of delimbing has been calculated by dry weight of remaining branches on the trees after delimbing. The trees reached the equilibrium dampness with approximately 40 days in the field, which directly reflected in the effectiveness of delimbing, which increased with decreased wood dampness. Despite being a uniquely developed machine for performing the delimbing, 55.6% of working time was spent on move, however, the average income of the forest delimbing was 643.34 m³/h, with an operating cost of R$ 180.04/hour, and the average cost of production R$ 0.28/m³.

Com o crescimento da economia brasileira a partir da década de 90, o setor florestal brasileiro passou por várias mudanças como a implantação de máquinas modernas em todo processo produtivo. No setor florestal uma das atividades consideradas mais importante é a colheita de madeira, visto que representa mais de 50% dos custos de produção. Com a introdução da colheita mecanizada no Brasil, tornam-se indispensáveis estudos para obtenção dados reais sobre as novas máquinas que estão surgindo no mercado. O objetivo deste estudo foi realizar a avaliação técnica e de custos de um desgalhador florestal de discos e sua eficácia no desgalhamento de árvores inteiras com diferentes teores de umidade. Na análise técnica foi realizado um estudo de tempos e movimentos pelo o método de cronometragem de tempos contínuos. Para a análise de custos foram calculados os custos operacionais através do método proposto pela ASABE. A eficácia do desgalhamento foi obtida pela determinação da massa seca de galhos remanescentes nas árvores após o desgalhamento. As árvores atingiram a umidade de equilíbrio aproximadamente aos 40 dias em campo, o que refletiu diretamente na eficácia do desgalhamento, que aumentava conforme diminuía o teor de umidade da madeira. Apesar de ser uma máquina desenvolvida unicamente para realização do desgalhamento, 55,6% do tempo de trabalho foi gasto com deslocamento, contudo, o rendimento médio do desgalhador florestal de discos foi de 643,34 m³/h, com custo operacional de R$ 180,04/hora, sendo, o custo de produção médio R$ 0,28/m³
Assessment of forest delimber in function of different dampness levels of eucalyptus wood
Keywords: Eucalipto; Colheita florestal; Maquinas florestais; Madeira - Efeito da umidade; Produtividade florestal; Forest machinery